2009
DOI: 10.1111/j.1465-7287.2009.00167.x
|View full text |Cite
|
Sign up to set email alerts
|

Wal‐mart, Leisure, and Culture

Abstract: "This essay contributes to the debate about the alleged spillover effects associated with Wal-Mart's growth. Combining county-level data on Wal-Mart entry and location from 1985 through 1998 with individual-level data on leisure activities, we estimate a positive relationship between Wal-Mart penetration and participation in activities involving inputs that can be bought at Wal-Mart. The relationship between Wal-Mart penetration and activities that do not involve inputs that can be bought at Wal-Mart is negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…This claim is inconsistent with the evidence, however. The thrust of the research agenda being pursued by McCloskey (2006, 2010) is to explain how and why virtue and prosperity are complements and self‐reinforcing inputs, and McCloskey's historical narrative receives some modern empirical support in the context of Wal‐Mart's effects on society (Carden et al ., 2009a, 2009b; Carden and Courtemanche, 2009; Courtemanche and Carden 2011).…”
Section: Robust (Liberal) Political Economy and The Shifting Critiquementioning
confidence: 99%
See 2 more Smart Citations
“…This claim is inconsistent with the evidence, however. The thrust of the research agenda being pursued by McCloskey (2006, 2010) is to explain how and why virtue and prosperity are complements and self‐reinforcing inputs, and McCloskey's historical narrative receives some modern empirical support in the context of Wal‐Mart's effects on society (Carden et al ., 2009a, 2009b; Carden and Courtemanche, 2009; Courtemanche and Carden 2011).…”
Section: Robust (Liberal) Political Economy and The Shifting Critiquementioning
confidence: 99%
“…Critics claim that Wal‐Mart may be able to offer lower prices, but the consequences of doing so include the depression of workers' wages and benefits, reductions in social capital and the elimination of small businesses (among other things). After examining the relationship between the per capita number of Wal‐Mart stores and various leisure activities, Carden and Courtemanche (2009) found that Wal‐Mart entry corresponds to an increase in the participation in activities that utilise goods that can be bought at Wal‐Mart (such as playing tennis or golf). Some evidence was found of a decrease in participation for activities that are unrelated to Wal‐Mart; however, no decrease – and maybe an increase – in participation was found for some cultural activities (specifically visiting an art museum or classical music concert).…”
Section: Robust (Liberal) Political Economy and The Shifting Critiquementioning
confidence: 99%
See 1 more Smart Citation
“…There is also a small but growing literature on the impact of Walmart on a variety of other outcomes outside of labor and housing markets. These include poverty rates (Goetz and Swaminathan, 2006), small business activity (Sobel and Dean, 2008), obesity (Courtemanche and Carden, 2011), social capital (Goetz and Rupasingha, 2006;Carden et al, 2009a), leisure activities (Carden and Courtemanche, 2009) and traditional values (Carden et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by this trend toward nontraditional retail outlets, a growing body of research examines the effects of Walmart on a number of outcomes, including prices (Basker 2005b;Basker and Noel 2009;Volpe and Lavoie 2007;Leibtag 2007, 2009), labor market outcomes (Basker 2005a;Hicks 2007;Neumark et al 2008;Dube et al 2007;Basker 2006), poverty (Goetz and Swaminathan 2006), small business activity (Sobel and Dean 2008), social capital (Goetz and Rupasingha 2006;Carden et al 2009a), leisure activities (Carden and Courtemanche 2009), traditional values (Carden et al 2009b), and obesity (Courtemanche and Carden 2011). 4 However, to our knowledge no previous research has used nationwide data to explore the effects of other big box chains.…”
mentioning
confidence: 99%